2020
DOI: 10.1108/jrf-08-2019-0146
|View full text |Cite
|
Sign up to set email alerts
|

Financial misconduct in Indian banks: what matters and what doesn’t?

Abstract: Purpose While several facets of financial misconduct have been explored, one aspect which has largely bypassed the attention of researchers is the factors affecting such misconduct behavior in banks. To investigate this in detail, this paper aims to use disaggregated data on Indian banks for an extended period to understand the factors driving such behavior. Design/methodology/approach Given the longitudinal nature of the data, the author uses fixed effects regression methodology which enables us to control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…World Bank speci es nancial inclusion (FI) is the state in which individuals and organizations have access to fairly priced nancial goods and services that meet their needs and are carried out ethically and sustainably. The nancial services mentioned in most of these reports are saving, borrowing, purchasing, also paying (Hanning and Jansen 2010; Ghosh and Ghosh 2014; Camara and Tuesta 2015; World Bank 2018) [11,9,6,23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…World Bank speci es nancial inclusion (FI) is the state in which individuals and organizations have access to fairly priced nancial goods and services that meet their needs and are carried out ethically and sustainably. The nancial services mentioned in most of these reports are saving, borrowing, purchasing, also paying (Hanning and Jansen 2010; Ghosh and Ghosh 2014; Camara and Tuesta 2015; World Bank 2018) [11,9,6,23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For this study, we also developed a corporate governance index using the principal component analysis (PCA) employing six different parameters and signals for exercising good governance practices [7]. The variables are board size, independent directors, board activity (meetings), directors' remuneration, the number of members in different committees and other company directorships (See Ghosh, 2020). A past study by Zattoni and Cuomo (2010) reported that the presence of independent directors raises transparency and information fairness about the firm and maximizes firm value.…”
Section: Data Description and Measurement Of Variablesmentioning
confidence: 99%
“…In other words, those who are in favor of frauds and perceive that their violent behavior would be accepted by their referent groups, have more chances to indulge in fraudulent activities. Large size of the banking institution and capital are the two principal factors that cause financial malpractices in public sector banks while board size and liquidity are more relevant for misconduct in private sector banks (Ghosh, 2020). Connivance between importer and exporter and loopholes in the issuing banks’ Letter of Credit (LC) system also create opportunity for the cunning importer and exporter to commit documentary credit fraud against banks (Han et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%